Psychological stress in geriatric patients with genito-urinary cancers. Issue 3 (May 2017) - Dräger, Désirée Louise; Protzel, Chris; Hakenberg, Oliver W.
Abstract: Background: Two-thirds of all cancer cases affect patients who are older than 65 years, yet the specific conditions of the treatment and supportive care in this age group are poorly studied. There are limited data on the specific psycho-oncological problems in elderly patients with genito-urinary cancers. The aim of this study was to investigate the psychosocial needs of elderly patients with genito-urinary tumors using screening questionnaires and to use such screening questionnaires for an in-patient psychosocial treatment program. Methods: Patients (≥ 65 years, n = 319) who underwent surgical (n = 295) or medical treatment (n = 24) for genito-urinary malignancies between 06/2014 and 11/2015 in our institution were included for prospective stress assessment. This was done with standardized questionnaires for stress screening and for the identification of need for care (NCCN Distress Thermometer and Hornheider Screening Instrument, HSI). Results: The patients scored an average of 4.4 on the Distress Thermometer. According to the survey evaluation, 28% of patients had need for psychosocial care. However, only a minority of patients (4%) did actually communicate any need for psychosocial care. We also assessed the actual utilization of inpatient psychosocial support which is offered to all patients. Conclusion: There is a significant number of elderly patients with genito-urinary cancer with increased psychological stress and a consecutive need of psychosocial care. This is underreported and underused by the patients. Therefore, an easy low-threshold access system with an interdisciplinary and inter-professional collaborative support system would be desirable. Measuring psychological distress systematically can be helpful in treating older patients with malignant diseases.